The Economic Consequences of Being Widowed by War: A Life-Cycle Perspective - Sebastian Till Braun; Jan Stuhler (Institute of Labor Economics (IZA), 2024)
Despite millions of war widows worldwide, little is known about the economic consequences of being widowed by war. We use life history data from West Germany to show that war widowhood increased women's employment immediately after World War II but led to lower employment rates later in life. War widows, therefore, carried a double burden of employment and childcare while their children were young but left the workforce when their children reached adulthood. We discuss the mechanisms contributing to this counterintuitive life-cycle pattern and examine potential spillovers to the next generation.
Keywords: J16; J20; N34; 330; war widows; labor market careers; female labor force participation; World War II